(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
Character education is very closely related to Islamic education. This research aims to discuss further how patterns change in character formation through the Independent Curriculum which is based on the Koran in Surah Az Zumar verse 18. This research uses a descriptive qualitative research approach through searching literature studies (library research). The data was obtained by studying verse 18 of Surah Az-Zumar from the Quran, then analyzed by reviewing the interview results and further examined with studies from reading sources. The research results show that the pattern of student character formation will be successful if it is planned as well as possible, this can be facilitated in the implementation of the independent curriculum in P5 activities at school. Through P5 activities, the school can design P5 activities according to school needs, allocated special time and refined with more comprehensive assessment instruments in assessing the process of student character development based on Surah Az Zumar verse 18 which says that humans have noble character and always do the best deeds, then they are people who have perfect reason